Antibacterial effect of biosynthesis silver nanoparticles on Pseudomonas aeruginosa - Qahtan Adnan Qader; Bashar Sadiq Noumi; Reyam Faris Saleh (Tikrit Journal of Pure Science)
The current study indicated  possibility  determining the inhibitory activity of silver nanoparticles which synthesis by the  Cinnamomum zeylanicum bark against 5 pathogenic bacterial isolates of to Multidrugs resistant Pseudomonas aeruginosa collected from hospitals (Azadi Education, Kirkuk General, Tuz General), Silver nanoparticles showed their inhibitory effect against bacteria by the Well diffusion method and The Diameter of inhibition zones ranged between (23-14)mm As for the growth inhibition assaysilver nanoparticles showed activity against the bacterial species at concentrations of ( 25,50, 75, 100)%, respectively through the absence of colony growth on the surface of the culture media at these concentrations Therefore it is possible to use nanoparticles synthesis from plants for some minerals due to their effective inhibitory properties that they have against bacteria.